Diagnosis and treatment of anemia in creole horses with two iron-rich diets - Guerra Delgado, Marco Sergio (2023)
The aim of this study was to diagnose and treat anaemia in Creole horses from the province of Piura, Peru. The study was conducted from June to December 2022. Anticoagulant blood samples were taken to determine haemoglobin, haematocrit, and erythrocyte values to identify individuals considered anemic. A total of 8 horses (4 female and 4 male) from 3 to 8 years old were selected. The animals were negative for anaplasmosis and piroplasmosis and were dewormed orally with 1% ivermectin. The animals were distributed into two groups and were fed two diets (D1 and D2), rich in iron, for 60 days. D1 contained 3.0 Mcal/kg, 18% protein, 4% fat, 8.5% fibre, 8% ash and 345 mg/kg iron and D2 contained 3.3 Mcal/kg, 18% protein, 4% fat, 15% fibre, 12% ash and 533.9 mg/kg of iron. At 30 and 60 days, the presence of anaemia was evaluated by haematological examination and body weight. The horses on Diet 1 increased (p<0.05) the haemoglobin concentration by 0.7 and 0.9 g/dL at 30 and 60 days, respectively, and gained 15.3 kg, while those on Diet 2 increased (p<0.05) the haemoglobin concentration in 0.8 and 1.5 g/dL, erythrocytes in 0.33 and 0.90x106/µL, and haematocrit in 2.1 and 5.1% at 30 and 60 days, respectively, and they gained 27.8 kg. It is concluded that Diet 2 made it possible to repair the problem of anaemia in the Creole horses of Piura.